Girl Let Me Tell You: Using Black Feminist Theory, Professional Counterspaces, and Endarkened Narrative Inquiry to Explore Narratives of Black Women Professional Staff in Higher Education - Fredrika Cowley (Adult Education Research Conference, 2023)
This presentation focuses on the theoretical framework and methodology utilized to explore the lived experiences of Black women professional staff in higher education and professional counterspaces as sites of resistance.
Keywords: Black feminist theory; Black women; professional counterspaces; endarkened narrative inquiry; professional staff